The Adoption Potential of Extended Lactation as a Strategy to Reduce Excess Calf Numbers in Dairy Farming - Josephine Gresham; Christoph Reiber; Mizeck G. G. Chagunda (Animals)
Dairy production relies predominantly on a few, selectively bred, high-yielding dairy breeds, resulting in a surplus of low-value male offspring. This situation leads to a conflict between a growing demand for milk and low appreciation for dairy calves. Extending lactation could reduce the number of calves born. This study aimed to assess the current use of extended lactation in dairy production in Southern Germany, identify the perceived potential, and determine the biological potential extended lactation has to reduce calf numbers. A survey from 2020 with 310 farmers was analysed. A total of 145 (46.8%) farmers used extended lactation. The use of extended lactation on farms correlated significantly with breed, milk yield, interest in continuing or implementing the use of extended lactation, and the indicated feasibility of extended lactation. The perceived potential was assessed by 39.8% of farmers as “high” to “very high”. A total of 17 (12.8%) farmers currently not using extended lactation were identified as potential adopters. Together with existing adopters, this could result in 52.3% of farms using extended lactation, which could biologically reduce calf numbers by 7.3% or 14.1% p.a., when extended by three or six months, respectively. This adoption potential shows that extended lactation can reduce calf numbers considerably, addressing both ethical and economic concerns in dairy farming and benefiting farmers as well as society.